Attack of the deranged mutant killer monster snow goons - Watterson, Bill (Calvin & Hobbes, 1992)
With the help of his faithful stuffed tiger companion and his alter egos--Spaceman Spiff, Stupendous Man, and Tracer Bullet--Calvin continues to navigate the tricky waters of youth.